In Vitro Antidiabetic Activity of Herbal Beverage Containing Turmeric and Guava Leaves - Nurdin, Samsu; Zuidar, Ahmad Sapta; Nurdjanah, Siti (Lembaga Penelitian dan Pengabdian Masyarakat, Institut Teknologi Sumatera, 2025)
Herbs have widely used in beverages. This study aimed to develop an herbal beverage for diabetics and to study the effect of guava leaves (G) and turmeric (K) proportions in an herbal beverage mixture on the inhibition of α-amylase and α-glucosidase enzyme activity and the organoleptic quality of the beverage. The proportions of G and K used in the beverage were C1: 0% G and 100% K; C2: 20% G and 80% K; C3: 40% G and 60% K; C4: 60% G and 40% K; C5: 80% G and 20% K; C6: 100% G and 0% K. The greater the proportion of K, the inhibition of the α-amylase enzyme increased. Increasing G proportion from 0% to 20% increased the inhibition of the α-glucosidase enzyme by 38.49% (from 21.05% to 59.54%), but no changes were observed on G proportion higher than 20%. Panelists’ reacted ‘dislike’ or ‘neither like nor dislike’ to the taste, aroma, and color of the beverages. The best beverage formulation with high inhibitory activities against α-amylase and α-glucosidase enzymes (64.15% and 68.58%, respectively) was a mixture of 40% G and 60% K, which was assessed to be ‘neither liked nor disliked’ in terms of taste, aroma, and color.